2014
DOI: 10.1007/s00429-014-0913-7
|View full text |Cite
|
Sign up to set email alerts
|

Congenital foot deformation alters the topographic organization in the primate somatosensory system

Abstract: Limbs may fail to grow properly during fetal development, but the extent to which such growth alters the nervous system has not been extensively explored. Here we describe the organization of the somatosensory system in a 6-year-old monkey (Macaca radiata) born with a deformed left foot in comparison to the results from a normal monkey (Macaca fascicularis). Toes 1, 3, and 5 were missing, but the proximal parts of toes 2 and 4 were present. We used anatomical tracers to characterize the patterns of peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…Another series of brainstem and spinal cord sections were processed for CTB staining to reveal label from tracer injections in digits 1, 3, and 5 of both hands. We used cytochrome oxidase (CO; Wong‐Riley, ) and vesicular glutamate transporter 2 (VGLUT2) staining (Liao et al, ; Qi et al, ) in separate series to reveal the architecture in the thalamus, brainstem, and spinal cord.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another series of brainstem and spinal cord sections were processed for CTB staining to reveal label from tracer injections in digits 1, 3, and 5 of both hands. We used cytochrome oxidase (CO; Wong‐Riley, ) and vesicular glutamate transporter 2 (VGLUT2) staining (Liao et al, ; Qi et al, ) in separate series to reveal the architecture in the thalamus, brainstem, and spinal cord.…”
Section: Methodsmentioning
confidence: 99%
“…We measured areas and optical intensities of CTB‐labeled regions in the brainstem cuneate nuclei on the two sides using ImageJ 64 software (National Institutes of Health, Bethesda, MD). The areas and optical intensities of CTB‐labeled regions on the two sides across the brainstem sections were statistically compared using the signed‐rank test (SigmaPlot 11.0, San Jose, CA; see Liao et al, ). Statistical significance was considered at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, apart from the hand, toes and feet were the most chosen body parts for cBCI control, even though only 6 (out of 9 selecting toes/feet) NMD and 2 (out of 7 selecting toes/feet) SO participants could still move their toes and/or feet to a certain extent. Another explanation could be the fact that feet are large body parts of which dexterity is evolutionarily close to that of the hand [44][45][46] and, therefore, easy to imagine/attempt control. Nevertheless, a biased choice for these body parts cannot be completely ruled out because feet and toes were the first and the last examples of 4 body parts shown in the animation video ("foot, head, tongue, or toes").…”
Section: Preferred Mental Strategiesmentioning
confidence: 99%
“…We investigated whether extreme habitual foot behavior might associate with organized toe maps in SI, where they have not been found in typically developed humans (Akselrod et al, 2017), although they are identified in monkeys (Liao et al, 2016;Nelson et al, 1980). Using 7 tesla neuroimaging during passive toe touch, we studied the foot representation of two individuals with developmental upper-limb amelia.…”
Section: Introductionmentioning
confidence: 99%